Retropupillary Iris Claw and Scleral-Fixated Intraocular Lens in the Management of Post-Cataract Aphakia - Vyas, Alok; Patel, Suhani; Tyagi, Mayank (Asian Journal of Medical Research, 2021)
Background: To compare retropupillary iris claw and scleral-fixated intraocular lens in the management of post-cataract aphakia. Subjects and Methods: Eighty- four patients of aphakia of either gender were classified into 2 groups of 42 each. Group I patients underwent retropupillary iris claw fixation and group II patients underwent scleral-fixated intraocular lens surgery. Parameters such as preoperative uncorrected distance visual acuity (UCDVA), best-corrected distance visual acuity (BCDVA), preoperative corneal edema, preoperative retinal pathology, interval between cataract surgery and IOL etc. were recorded in both groups. Results: There were 22 males and 20 females in group I and 18 males and 24 females in group II. The mean preoperative UCDVA was 1.54 in group I and 1.72 in group II. Preoperative corneal edema was seen in 10 in group I and 4 in group II. Preoperative retinal pathology was seen in 14 in group I and 6 in group II. Interval between cataract surgery and IOL was 1.2 months in group I and 7.6 months in group II. IOL placed at time of cataract surgery was seen in 23 in group I and 6 in group II. UCDVA at 1 month in group I was 0.9 and in group II was 0.8. BCDVA at 1 month was 0.8in group I and 0.4 in group II. UCDVA at 1 year was 0.7 in group I and 0.8 in group II. BCDVA at 1 year was 0.5 in group I and 0.4 in group II. Complications was postoperative CME seen in 2 in group I and 5 in group II, transient hypotony was seen 5 in group I and 11 in group II, spike in IOP was seen 4 in group I and 0 in group II, severe iridocyclitis in 5 in group I and 1 in group II, retinal detachment in 2 in group I and 1 in group II, endophthalmitis in 1 in group I and 0 in group II and re-surgery in 1 in group I and 3 in group II. Conclusion: Retropupillary iris claw IOL fixation technique is equivalent to SFIOL for visual rehabilitation of post cataract aphakia.